Chemical and bioactive characterization of spanish and belgian apple pomace for its potential use as a novel dermocosmetic formulation - Alvarez Arraibi, Ana (2021)
Currently, there is a general trend towards reutilizing industrial by-products that would otherwise be discarded or considered as waste, aiming to explore them as alternative sources of valuable compounds. The apple pomace remaining from cider and apple juice industries represents a high-potential source of bioactive compounds with putative application in food or pharmaceuticalrelated products. Accordingly, the work reported herein was conducted to characterize the phenolic compounds in apple pomace from Belgium and Spain, as well as to evaluate its chemical composition and particular types of bioactivity. As a proof of concept, a new hydrogel was prepared, incorporated with the bioactive compounds and pectin extracted from apple pomace, aiming to obtain the most organic formulation possible. Independently of the extracting agent, it became evident that using lyophilization as the drying step is a better choice than thermal processes as it yielded a richer phenolic profile (fifteen individual compounds), with 5-O-caffeoylquinic acid as the major compound (66 to 114 mg/100 g dw) in Belgian samples. In general, the hydroethanolic extracts showed the strongest antioxidant and antimicrobial (particularly against Propionibacterium acnes: MIC = 2.5 mg/mL) activities. This result, together with the lipid nature of human skin, led it to be chosen as the extract type to be incorporated in the hydrogel. In general, apple pomace stood out as a valuable source of bioactive compounds, especially polyphenols and pectin, with good potential to be incorporated in dermal formulations.